An Overview on Silicon Valley Bank Failure in Europe: Causes and Effects - Federico, Domenica; Napoli, Francesco; Notte, Antonella (Contemporary Research in Business, Management and Economics Vol. 5, 2024)
This chapter examines how Europe reacted to the collapse of Silicon Valley Bank (SVB). The SVB was specialized in banking for technological startups, and it provided financing for almost half of US venture-backed technology. On the 10th of March, SVB collapsed, the second-largest failure since the financial crisis of 2008. The banking failures can significantly impact the financial system and the financial markets, affecting depositors and investors’ confidence. In this chapter, the Silicon Valley Bank failure is analyzed as a case study. We describe the main causes that contributed to the collapse of SVB, examining the consequences in Europe in terms of effects on financial systems, markets, and startup ecosystem, as well as in terms of reactions from supervisory authorities. The results show that the lack of a risk culture and a limited specific knowledge of the dynamics of the sector generated disastrous consequences, leading to the collapse of SVB. This chapter contributes to the literature highlighting how political events can have significant impacts on the way financial institutions are regulated and supervised. The study represents a starting point for investigating the consequences of the SVB bankruptcy, increasing the reflections on effects of the failure in Europe with other factors that can affect financial systems and market to formulate any new hypotheses for further future studies.